2022
DOI: 10.4235/agmr.21.0095
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Otago Exercise Program on Frailty and Empowerment in Older Nursing Home Residents: A Randomized Controlled Trial

Abstract: Ethical approval:The study protocol was approved by the Ethics Committee of Ege University Faculty of Medicine (Number 70198063-050.06.04). All procedures performed in studies involving human participants were in accordance with the 1964 Declaration of Helsinki and its later amendments or comparable ethical standards .Informed consent: All of the patients were informed of the study protocols in detail and provided their informed written consent .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…The OEP prioritizes strengthening the muscles used in knee flexion and extension, hip abduction, and ankle dorsiflexion and plantarflexion. [25] As seen by the mean improvement of 67% in the lower limb muscle strength of those living in NHs in our results, thus, this training approach fits the demands of these elders to enhance and maintain normal muscle strength.…”
Section: Postural Control Ability In Elders Living In the Nhsupporting
confidence: 73%
See 3 more Smart Citations
“…The OEP prioritizes strengthening the muscles used in knee flexion and extension, hip abduction, and ankle dorsiflexion and plantarflexion. [25] As seen by the mean improvement of 67% in the lower limb muscle strength of those living in NHs in our results, thus, this training approach fits the demands of these elders to enhance and maintain normal muscle strength.…”
Section: Postural Control Ability In Elders Living In the Nhsupporting
confidence: 73%
“…The health status was tested by the number of frail elders in 2 studies with 147 participants, including 70 in the OEP group and 77 in the control group. [18,25] The meta-analysis confirmed that the number of frail elders reduced significantly in the OEP group compared to the control group (risk ratio = 0.35; 95% CI = 0.18, 0.66; I 2 = 0%; P = .001; Fig. 9).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“… 4 , 5 ) Moreover, functional limitations and frailty are associated with low cognitive performance. 6 , 7 ) Although methods exist for preventing frailty, such as exercise or the development of guidelines on primary prevention, 8 , 9 ) early risk screening can enhance the effectiveness of these prevention methods. Therefore, screening and monitoring tools for early detection and periodic follow-up are important for effective disease prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%